Sand control in well construction and operation - Matanovic, Davorin (Springer environmental science and engineering, 2012)
Produced sand causes a lot of problems. From that reasons sand production must be monitored and kept within acceptable limits. Sand control problems in wells result from improper completion techniques or changes in reservoir properties. The idea is to provide support to the formation to prevent movement under stresses resulting from fluid flow from reservoir to well bore. That means that sand control often result with reduced well production. Control of sand production is achieved by: reducing drag forces (the cheapest and most effective method), mechanical sand bridging (screens, gravel packs) and increasing of formation strength (chemical consolidation). For open hole completions or with un-cemented slotted liners/screens sand failure will occur and must be predicted. Main problem is plugging. To combat well failures due to plugging and sand breakthrough Water-Packing or Shunt-Packing are used.